Cytotoxic Effect of Immunotoxin Containing The Truncated Form of Pseudomonas Exotoxin Cell Lines - Elahe Safari; Ahmad Zavaran Hosseini; Zuhair Hassan; Khosro Khajeh; Mehdi Shafiee Ardestani; Behzad Baradaran (Cell Journal, 2014)
Objective: Immunotoxins (ITs) have been developed for the treatment of cancer, and comprise of antibodies linked to toxins. Also vascular endothelial growth factor (VEGF) plays a key role in tumor angiogenesis, and the blockade of VEGF receptor-2 (VEGFR2) inhibits angiogenesis and tumor growth. The aim of this study was to produce anti-VEGFR2/rPE (Pseudomonas exotoxin) 38 IT to test its cytotoxic activity and mechanism of action. Materials and Methods: In this basic research and experimental study, at first, DNA that encodes recombinant PE38 protein was inductively expressed in Escherichia coli (E.coli) and purified by nickel-sepharose chromatography and further analyzed by western blot. Then, for production of IT, rPE38 was chemically conjugated to anti-VEGFR2. The cytotoxicity response of IT treatment was evaluated by 3-(4,5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide (MTT) test in Human Umbilical Vein Endothelial Cell (HUVEC) and Michigan Cancer Foundation-7 (MCF-7) (VEGFR2+) cell lines. The mechanism of IT cytotoxicity was observed by Annexin V staining and flow cytometry. Continuous variables were compared with the analysis of variance (ANOVA; for all groups). P values less than 0.05 were considered statistically significant. Results: SDS-PAGE showed 98% purity of rPE38 and IT. In vitro dose-dependent cytotoxicity assay demonstrated that anti-VEGFR2/PE38 is toxic to VEGFR2-positive cells. IT treatment significantly inhibited proliferation of HUVEC and MCF-7 in a VEGFR2-specific manner as compared with the control groups (p<0.05). Flow cytometry showed that the mechanism of IT induced cell death is mediated by apoptosis. Conclusion: IT treatment also caused remarkable synergistic cytotoxicity characterized by decreased cell viability, and an increased apoptotic index by both anti-VEGFR2 and PE38. Thus these results raise the possibility of using anti-VEGFR2/PE38 IT for cancer therapy because nearly all tumors induce local angiogenesis with high VEGFR expression.